2022
DOI: 10.24036/vomek.v4i4.471
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Prestasi Belajar, Dukungan Sosial Orang Tua Dan Ekspektasi Kerja Terhadap Minat Melanjutkan Studi S2 Pada Mahasiswa Pendidikan Teknik Mesin Ft Unp

Abstract: Penelitian bertujuan mengungkapkan hubungan prestasi belajar, social support orang tua dan harapan bekerja pada minat melanjutkan studi S2 pada mahasiswa Pendidikan Teknik Mesin FT-UNP. Jenis penelitian yang diberlakukan ialah quantitative research. Subjek penelitian ialah mahasiswa Pendidikan Teknik Mesin Angkatan 2018 FT-UNP sebanyak 76 mahasiswa. Teknik pengumpulan data memakai kuisioner (angket) dan dokumentasi. Teknik analisis data memakai metode correlational analysis. Hasil penelitian memperlihatkan: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The study findings explore the variable of job expectations, which has a positive effect on S2 interest, which is in line with the statement of Indriyanti et al, (2013) that one of the interests is influenced by future expectations, then Rochmah (2021) also states that job expectations affect the continuation of S2 interest. Further relevant research by Azhar et al (2022), Ulfa (2019), andSuharmi et al (2021) support the findings of this study, namely that job expectations have a positive effect on master's interest. The results of a study of final year students at the Ghana of University, Legon by Mahama et al, (2013) confirm that subjective job uncertainty in the assessment of job expectations has an impact on student interest in joining a postgraduate program.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The study findings explore the variable of job expectations, which has a positive effect on S2 interest, which is in line with the statement of Indriyanti et al, (2013) that one of the interests is influenced by future expectations, then Rochmah (2021) also states that job expectations affect the continuation of S2 interest. Further relevant research by Azhar et al (2022), Ulfa (2019), andSuharmi et al (2021) support the findings of this study, namely that job expectations have a positive effect on master's interest. The results of a study of final year students at the Ghana of University, Legon by Mahama et al, (2013) confirm that subjective job uncertainty in the assessment of job expectations has an impact on student interest in joining a postgraduate program.…”
Section: Resultssupporting
confidence: 82%
“…In line with the statement Indriyanti et al, (2013) that the interest in continuing master's studies is influenced by the factor of future expectations, as for Rochmah (2021) also stated that job expectations affect the interest in continuing education for S2 level. Some empirical studies conducted by Sumakta (2015), Ulfa (2019), Suharmi et al (2021), Rochmah (2021), andAzhar et al (2022) found that job expectations affect interest in continuing education. It is proven that job expectations can encourage efforts to achieve a performance where job expectations can have a positive effect on interest in continuing studies to the next level.…”
Section: Introductionmentioning
confidence: 99%